Iron-based composite binder for pelletizing of iron ore difficult to pelletize and pelletizing method of iron ore difficult to pelletize
By using iron-based composite adhesives in pellet production, the problem of low proportion of pelletized iron ore is solved, the effect of improving the proportion and ensuring the iron grade and compressive strength of finished pelletized ore is achieved, and the economic benefits of pelletized ore are improved.
Patent Information
- Application Number
- CN202411986840.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-18
AI Technical Summary
In the prior art, the ratio of iron ore is generally not high during the production process of pellets. To increase the ratio requires significantly increasing the amount of bentonite binder, resulting in a significant decrease in the iron grade and economic benefits of finished pellet ore.
An iron-based composite binder is used, which consists of fine-grain magnet concentrate, bentonite, humic acid, sodium carboxymethylcellulose and borax. Through the synergistic effect of these components, the mineral particle properties and bonding properties are improved, the ratio of difficult-to-pole iron ore is improved, and the iron grade of the finished pellet ore is ensured.
By using iron-based composite adhesive, the ratio of difficult-to-pole iron ore can be improved without reducing the performance of pellet growth, ensuring that the iron grade and compressive strength of the finished pellet ore reaches an excellent level, and improving the economic benefits of the pellet ore.
Abstract
Description
Technical Field
[0001] The invention relates to an iron-based composite binder, in particular to an iron-based composite binder for pelletizing hard-to-pellet iron ore, and also to a method for pelletizing hard-to-pellet iron ore using the iron-based composite binder, belonging to the technical field of pellet production. Background Art
[0002] Pellet ore has excellent metallurgical properties and is one of the main blast furnace ironmaking materials. At present, some countries have achieved a high proportion or even global pellet smelting, which can improve ironmaking efficiency and reduce production energy consumption. However, the overall proportion of pellets entering the furnace in China is relatively low, and there is still considerable room for development.
[0003] Domestic iron ore resources generally have the characteristics of "poor, fine, mixed and scattered", which is one of the reasons why the development of pellets is restricted. At the same time, the output of difficult-to-pellet iron concentrates such as hematite, specularite, and sulfuric acid slag is large, the grade is high, and the particle size is fine. However, the main component of these iron concentrates is iron oxide, and the crystallization process is poor. High temperature is required to obtain high pellet strength. At the same time, their ball forming ability is poor. Compared with ordinary iron concentrates, the performance of the prepared green balls is not good. In order to ensure the quality of green balls, a high proportion of bentonite needs to be added. If you want to achieve a high proportion of difficult-to-pellet iron concentrate to prepare high-quality pellets, the proportion of bentonite needs to be further increased, which will inevitably lead to a significant decrease in iron grade, thereby affecting economic benefits. Therefore, the main difficulty in the production of difficult-to-pellet iron concentrate pellets lies in the development of high-quality and efficient binders and the strengthening of the consolidation behavior of pellets during the roasting process.
[0004] With the increasing shortage of high-quality iron ore concentrate resources and the demand for large quantities of high-quality pellets in blast furnaces, the use of refractory iron ores such as hematite, specularite, and sulfate slag for pellet preparation is an important development direction for blast furnace charge preparation. Therefore, developing binders for refractory iron ores to strengthen the raw ball properties and high-temperature consolidation behavior of pellets to prepare high-quality pellets is of great practical significance for reducing the external dependence on iron ore resources and achieving the dual carbon goals of the steel industry. Summary of the invention
[0005] In view of the problem that the ratio of difficult-to-ballize iron ore in the pellet production process in the prior art is generally not high, and increasing the ratio requires a significant increase in the amount of bentonite binder added, which leads to a significant decrease in the iron grade and economic benefits of the finished pellets. The first purpose of the present invention is to provide an iron-based composite binder, which can effectively improve the properties of mineral particles and the bonding performance between mineral particles and the binder, and can meet the requirements for preparing pellets with high-ratio difficult-to-ballize iron ore concentrate, while improving the performance of raw balls and finished balls, ensuring the iron grade of the finished pellets.
[0006] The second object of the present invention is to provide a method for pelletizing difficult-to-ballize iron ore. The method does not change the existing pelletizing production process, but uses an iron-based composite binder instead of conventional bentonite for pelletizing. The method can strengthen the physical and chemical interaction between the binder and the surface of the iron ore concentrate particles to achieve the purpose of improving the raw ball performance. At the same time, the performance of the finished ball is also improved, and the iron grade of the finished pellet ore can be guaranteed.
[0007] In order to achieve the above technical purpose, the present invention provides an iron-based composite binder for pelletizing refractory iron ore, which comprises fine-grained magnetite concentrate, bentonite, humic acid, sodium carboxymethyl cellulose and borax.
[0008] The key to the iron-based composite binder of the present invention is to use fine-grained magnetite concentrate, bentonite, humic acid, sodium carboxymethyl cellulose and borax in combination to give full play to the synergistic effect of the components, wherein the fine-grained magnetite concentrate as a mineral carrier can adsorb other binder components on its surface, thereby better exerting the bonding effect of various bonding components, ensuring the stability of the iron-based composite binder effect, and at the same time, the fine-grained magnetite concentrate is fully dispersed inside the pellet by utilizing the bonding effect of the binder, and the high dispersion of the fine-grained magnetite concentrate is more conducive to exerting its effect, and its oxidation and heat release in the high-temperature process can better improve the heat distribution inside the pellet, and at the same time, the oxidation recrystallization of ferroferric oxide helps to improve the consolidation behavior of the pellet, and can also improve the iron grade of the pellet to a certain extent. Humic acid, sodium carboxymethyl cellulose and borax, as modified ingredients of bentonite bonding, can strengthen the bonding effect of bentonite, improve the properties of mineral particles and the bonding performance between mineral particles and binder, so that under the condition of low iron-based composite binder dosage, the proportion of refractory iron ore can be increased and the quality of raw balls can meet the requirements. The additional calcium-magnesium-silicon-aluminum gangue component introduced by increasing the proportion of refractory iron ore compensates for the negative impact brought about by the reduction of low iron-based composite binder dosage, so that the quality of the finished pellets is not significantly affected.
[0009] As a preferred solution, the iron-based composite binder is composed of the following mass percentage components: fine-grained magnetite concentrate 20%~60%, bentonite 20%~70%, humic acid 5%~20%, sodium carboxymethyl cellulose 1%~5%, borax 1%~5%. If the mass proportion of fine-grained magnetite concentrate is low, the consolidation effect cannot be fully improved, and the effect of improving the iron grade is not obvious. If the mass proportion of fine-grained magnetite concentrate is too high, the effect of the composite binder will be reduced, and the composite binder ratio needs to be increased. Bentonite is the main binder component. If its mass proportion is low, the bonding performance of the composite binder is poor. If its proportion is high, it is difficult to give full play to the synergistic bonding effect between the organic-inorganic binder in the composite binder. Humic acid, sodium carboxymethyl cellulose and borax are organic components that can improve the bonding effect. If their mass content is too low, the synergistic effect between the organic-inorganic binder cannot be fully exerted. If their mass proportion is too high, the organic component is easy to reduce the pellet strength during the decomposition process. In particular, the introduction of borax is beneficial to the formation of a low melting point phase, which helps to improve the strength and metallurgical properties of the pellets.
[0010] As a preferred solution, the particle size of the fine-grained magnetite concentrate satisfies the requirement that the mass of the -10 μm particle size accounts for more than 90%. The introduction of magnetite concentrate can effectively improve the iron grade of the iron-based binder. The particle size of the magnetite concentrate is within the preferred range, which is more conducive to the uniform dispersion of the magnetite concentrate in the entire pellet raw material, thereby being more conducive to uniform oxidation and heat release inside the pellet during the high-temperature process to improve the heat distribution inside the pellet, and at the same time, it can also improve the problem of insufficient solid phase consolidation of the main component of ferric oxide in the difficult-to-spheroidize iron ore by forming ferroferric oxide oxidation recrystallization.
[0011] The present invention also provides a method for pelletizing refractory iron ore, which comprises preparing the iron-based composite binder into a slurry, adding the slurry into a pelletizing raw material including the refractory iron ore, and mixing and pelletizing the raw balls obtained by heat treatment to obtain finished balls.
[0012] The method for pelletizing difficult-to-ballize iron ore provided by the present invention utilizes an iron-based composite binder to replace conventional bentonite for pelletizing without changing the existing pelletizing production process. The iron-based composite binder can strengthen the physical and chemical effects between the binder and the surface of the iron concentrate particles to achieve the purpose of improving the raw ball performance. At the same time, the performance of the finished ball is also improved, and the iron grade of the finished pellet ore can be guaranteed.
[0013] As a preferred solution, the slurry is prepared by the following method: fine grinding and nano-grinding the magnetite concentrate to obtain fine-grained magnetite concentrate; the fine-grained magnetite concentrate powder is mixed with bentonite, humic acid, sodium carboxymethyl cellulose, borax and water and ultrasonically treated to obtain a slurry.
[0014] As a preferred solution, the conditions of the ultrasonic treatment are: temperature of 40-80°C, ultrasonic frequency of 25-30KHz, and ultrasonic treatment time of 15-30min. Ultrasonic treatment is conducive to the adsorption of binder components such as humic acid, sodium carboxymethyl cellulose and borax on the surface of ultrafine magnetite concentrate particles. Magnetite concentrate powder particles, as binder carriers, can better play their bonding role, ensure the stability of the iron-based composite binder effect, and at the same time, the bonding effect of the binder is utilized to achieve uniform dispersion of ultrafine magnetite concentrate particles inside the pellets.
[0015] As a preferred solution, the apparent viscosity of the slurry at room temperature is 2000-20000 mPa•s, the pH value is not less than 8, and the potential is between -60 mV and -45 mV.
[0016] As a preferred solution, the amount of the slurry added to the pellet raw material is measured by the dry basis mass of the slurry accounting for 1% to 3% of the dry basis mass of the pellet raw material. The amount of the binder can be adjusted according to the raw ball performance. Compared with the existing bentonite, the binder can achieve a better bonding effect with a smaller amount.
[0017] As a preferred solution, the refractory ductile iron ore includes at least one of hematite, specularite, and sulfate slag; the refractory ductile iron ore has an iron grade of 52% to 69% and a specific surface area of not less than 1000 cm 2 / g, and the mass proportion of particle size meeting the -0.074mm particle size grade is not less than 85%.
[0018] As a preferred solution, the mass of the refractory iron ore does not exceed 60% of the total mass of the iron concentrate in the pellet raw material. Since the consolidation effect of the refractory iron concentrate during the roasting process is poor, an excessively high ratio will lead to a decrease in the compressive strength of the finished balls, affecting secondary sales or subsequent blast furnace smelting efficiency. The present invention is based on the use of an iron-based composite binder, which can increase the mass proportion of the refractory iron concentrate in the iron concentrate contained in the pellet raw material to more than 30%, preferably more than 40%, and more preferably 50% to 60%, while also being able to obtain qualified raw balls and finished balls, which is a significant improvement.
[0019] The heat treatment process of the present invention includes conventional operations such as drying, preheating, roasting and cooling in the pellet production process.
[0020] The green ball prepared by the iron-based composite binder of the present invention has a drop strength of not less than 3 times (0.5m per ball). -1 The compressive strength of the finished pellets is not less than 2500N per -1 , the iron grade is not less than 60%. The performance of the raw balls meets the requirements of the transportation process, the compressive strength of the finished balls can meet the subsequent uses, and the iron grade remains at a high level.
[0021] Compared with the prior art, the technical solution of the present invention has the following beneficial effects: The iron-based composite binder provided by the present invention is composed of magnetite concentrate powder and bentonite, humic acid, sodium carboxymethyl cellulose, borax, etc. The composite binder has a significantly better bonding effect on mineral particles than conventional bentonite bonding. By using the iron-based composite binder, the performance of the raw balls is not affected while the proportion of the hard-to-ball iron ore is increased, and the quality of the finished balls can also be guaranteed. For example, when the proportion of the hard-to-ball iron concentrate is increased to 60%, the proportion of the composite binder is 2%, and the drop strength of the raw balls is not less than 4 times (0.5m per ball). -1 The compressive strength of the finished pellets is greater than 2500 N per -1 , the iron grade of the finished pellets shall not be less than 60%. DETAILED DESCRIPTION
[0022] The following examples are intended to further illustrate the present invention, rather than to limit the scope of protection of the claims of the present invention.
[0023] Example 1 40% of the magnetite concentrate after fine grinding and nano-grinding (-10μm particle size accounts for 95% by mass), 50% bentonite, 6% humic acid, 2% sodium carboxymethyl cellulose, and 2% borax were ultrasonicated at 25KHz for 30 minutes in a 75℃ water bath to obtain an iron-based composite binder slurry. The slurry has an apparent viscosity of about 5000mPa•s at room temperature, a pH value of 9.5, and a potential of about -50mV. 30% of the sulfate slag (mainly hematite, with an iron grade of 60.47%, a silicon dioxide content of 6.52%, and a specific surface area of about 1500cm 2 / g, -0.074 mm particle size accounts for 90% by mass) and 70% conventional magnetite concentrate (-0.074 mm particle size accounts for 85% by mass), add 1.6% iron-based composite binder slurry, mix well and add water to make balls, the green ball particle size is 8~12mm, and the green ball drop strength is 3.2 times·(0.5m·piece) -1 The pellets were dried at 105°C, preheated at 950°C for 10 minutes, calcined at 1250°C for 10 minutes, heated at 1100°C for 2 minutes, and cooled at room temperature. The compressive strength of the finished pellets is 3240 N per piece. -1 The iron grade of the finished pellet ore is 64.88%.
[0024] Example 2 45% of the magnetite concentrate (-10μm particle size accounts for 94% of the mass) after fine grinding and nano-grinding, 40% bentonite, 10% humic acid, 2% sodium carboxymethyl cellulose, and 3% borax were ultrasonicated at 25KHz for 30 minutes in a 75℃ water bath to obtain an iron-based composite binder slurry. The slurry has an apparent viscosity of 7000mPa•s at room temperature, a pH value of 10.2, and a potential of about -60mV. 50% of the sulfate slag (mainly hematite, with an iron grade of 60.47%, a silicon dioxide content of 6.52%, and a specific surface area of about 1500cm 2 / g, -0.074mm particle size accounts for 90% by mass) and 50% conventional magnetite concentrate (-0.074mm particle size accounts for 85% by mass), add 2% iron-based composite binder slurry, mix well and add water to make balls, the green ball particle size is 8~12mm, and the green ball drop strength is 3.3 times·(0.5m·piece) -1 The pellets were dried at 105°C, preheated at 950°C for 10 minutes, calcined at 1250°C for 10 minutes, heated at 1100°C for 2 minutes, and cooled at room temperature. The finished pellets have a compressive strength of 2940 N·pcs -1 The iron grade of the finished pellet ore is 62.85%.
[0025] Example 3 50% of the magnetite concentrate after fine grinding and nano-grinding (-10μm particle size accounts for 96% by mass), 35% bentonite, 10% humic acid, 4% sodium carboxymethyl cellulose, and 1% borax were ultrasonicated at 25KHz for 30 minutes in a 75℃ water bath to obtain an iron-based composite binder slurry. The slurry has an apparent viscosity of about 10000mPa•s at room temperature, a pH value of 10.5, and a potential of about -48mV. 60% of the sulfate slag (mainly hematite, with an iron grade of 60.47%, a silicon dioxide content of 6.52%, and a specific surface area of about 1500cm 2 / g, -0.074 mm particle size accounts for 90% by mass) and 40% conventional magnetite concentrate (-0.074 mm particle size accounts for 85% by mass), add 2% iron-based composite binder slurry, mix well and add water to make balls, the green ball particle size is 8~12 mm, and the green ball drop strength is 3.1 times·(0.5m·piece) -1 The pellets were dried at 105°C, preheated at 950°C for 10 minutes, calcined at 1250°C for 10 minutes, heated at 1100°C for 2 minutes, and cooled at room temperature. The compressive strength of the finished pellets is 2690 N·pcs -1 The iron grade of the finished pellet ore is 63.09%.
[0026] Comparative Example 1 30% sulfate slag (mainly hematite, iron grade 60.47%, silicon dioxide content 6.52%, -0.074 mm particle size accounts for 90% by mass) is mixed with 70% conventional magnetite concentrate (-0.074 mm particle size accounts for 85% by mass), 2.5% bentonite is added, mixed and water is added to make balls, the particle size of the green balls is 8~12 mm, and the drop strength of the green balls is 3.2 times (0.5m per ball) -1 The pellets were dried at 105°C, preheated at 950°C for 10 minutes, calcined at 1250°C for 10 minutes, heated at 1100°C for 2 minutes, and cooled at room temperature. The finished pellets had a compressive strength of 2990 N·pcs -1 The iron grade of the finished pellet ore is 63.47%.
[0027] By comparing this comparative example with Example 1, it can be seen that when bentonite is used as a binder, under the condition of a higher ratio of high binder addition, the ratio of sulfate slag is low, and the compressive strength of the finished pellets is also relatively low.
[0028] Comparative Example 2 50% sulfate slag (mainly hematite, iron grade 60.47%, silicon dioxide content 6.52%, -0.074 mm particle size accounts for 90% by mass) is mixed with 50% conventional magnetite concentrate (-0.074 mm particle size accounts for 85% by mass), 3.5% bentonite is added, mixed and water is added to make balls, the particle size of the green balls is 8~12 mm, and the drop strength of the green balls is 3.3 times·(0.5m·piece) -1 The pellets were dried at 105℃, preheated at 950℃ for 10 minutes, roasted at 1250℃ for 10 minutes, heated at 1100℃ for 2 minutes, and cooled at room temperature. The compressive strength of the finished pellets is 2550 N per piece. -1 The iron grade of the finished pellet ore is 61.39%.
[0029] By comparing this comparative example with Example 3, it can be seen that when bentonite is used as a binder, when the ratio of sulfate slag is high, the amount of bentonite added increases, and the iron grade and compressive strength of the obtained pellets decrease significantly.
[0030] Comparative Example 3 Compared with Example 3, the only difference is that no fine-grained magnetite concentrate is added to the composite binder, and the specific composition is: 85% bentonite, 10% humic acid, 3% sodium carboxymethyl cellulose, and 2% borax. Other operations and conditions are the same as in Example 3.
[0031] The compressive strength of the finished ball is 2430N per piece -1 The iron grade of the finished pellets is 62.58%. The results show that if fine-grained magnetite concentrate is not introduced into the composite binder, the compressive strength of the pellets will decrease significantly.
[0032] Comparative Example 4 Compared with Example 3, the only difference is that fine-grained magnetite concentrate that has not been subjected to nano-grinding is added to the composite binder, and the specific composition is: 40% magnetite concentrate (-74 μm particle size accounts for 90% by mass), 50% bentonite, 6% humic acid, 2% sodium carboxymethyl cellulose, 2% borax, and the addition amount of the composite binder to the iron concentrate raw material is 2.5%. Other operations and conditions refer to Example 3.
[0033] The compressive strength of the finished ball is 2580 N per piece. -1 The iron grade of the finished pellet ore is 62.37%.
[0034] The results show that, compared with Example 3, the introduction of magnetite concentrate into the composite binder significantly reduces the compressive strength of the pellets. Compared with Example 3, the introduction of fine-grained magnetite concentrate into the composite binder significantly improves the compressive strength of the pellets.
Claims
1. An iron-based composite binder for pelletizing refractory iron ore, characterized in that: Contains fine grade magnetite concentrate, bentonite, humic acid, sodium carboxymethyl cellulose and borax.
2. The iron-based composite binder for pelletizing refractory iron ore according to claim 1, characterized in that: The invention is composed of the following components in mass percentage: 20% to 60% of fine-grained magnetite concentrate, 20% to 70% of bentonite, 5% to 20% of humic acid, 1% to 5% of sodium carboxymethyl cellulose and 1% to 5% of borax.
3. An iron-based composite binder for pelletizing refractory iron ore according to claim 1 or 2, characterized in that: The particle size of the fine-grained magnetite concentrate meets the requirement that the mass fraction of the -10 μm particle size exceeds 90%.
4. A method for pelletizing refractory iron ore, characterized in that: After the iron-based composite binder according to any one of claims 1 to 3 is made into a slurry, it is added to the pelletizing raw materials including the refractory iron ore and mixed to form pellets. The obtained green balls are subjected to heat treatment to obtain finished balls.
5. The method for pelletizing refractory iron ore according to claim 4, characterized in that: The slurry is prepared by the following method: fine grinding and nano-sand grinding are performed on magnetite concentrate to obtain fine-grained magnetite concentrate; the fine-grained magnetite concentrate is mixed with bentonite, humic acid, sodium carboxymethyl cellulose, borax and water, and ultrasonically treated to obtain slurry.
6. The method for pelletizing refractory iron ore according to claim 5, characterized in that: The ultrasonic treatment conditions are: temperature of 40-80° C., ultrasonic frequency of 25-30 KHz, and ultrasonic treatment time of 15-30 min.
7. A method for pelletizing refractory iron ore according to any one of claims 4 to 6, characterized in that: The slurry has an apparent viscosity of 2000-20000 mPa•s at room temperature, a pH value of not less than 8, and a potential between -60 mV and -45 mV.
8. The method for pelletizing refractory iron ore according to claim 4, characterized in that: The amount of the slurry added to the pelletizing raw material is measured by taking the dry basis mass of the slurry as 1% to 3% of the dry basis mass of the pelletizing raw material.
9. The method for pelletizing refractory iron ore according to claim 4, characterized in that: The refractory spheroidal iron ore comprises at least one of hematite, specularite and sulfate slag; The iron grade of the refractory spheroidal iron ore is 52% to 69%, and the specific surface area is not less than 1000cm 2 / g, and the mass proportion of particle size meeting the -0.074mm particle size grade is not less than 85%.
10. A method for pelletizing refractory iron ore according to claim 4 or 9, characterized in that: The mass of the refractory iron ore does not exceed 60% of the total mass of the iron ore concentrate in the pelletizing raw material.
Citation Information
Cited By
Aluminum-titanium-based composite bonding slurry, preparation method thereof and application of aluminum-titanium-based composite bonding slurry in fluorine-containing iron ore pellets
CN119876589A
Magnesium-based composite binder, preparation method thereof and application of magnesium-based composite binder in iron ore pellets
CN119876591A